African American Perceptions of Participating in Health Research Despite Historical Mistrust. (19th January 2023) - Statler, Marie Campbell; Wall, Barbra Mann; Richardson, Jeanita W.; Jones, Randy A.; Kools, Susan
Abstract : A qualitative descriptive approach examined perspectives of African Americans (AA) on their participation in health research despite historical research mistreatment. Nineteen AAs participated in semistructured interviews that provided data that were analyzed using thematic analysis. Salient themes included race concordance, being respected and valued by the researcher, research participation motivators, and cultural experiences of racism in health care. This study challenges dominant ideology that AAs are unwilling to participate in research and offers solutions to promote research inclusive of their perceptions. Therefore, researchers need to design research with inclusiveness and transparency that openly displays how research will impact future generations.